One within Many, Many within One: A Collaborative, Dialogical Exploration of Librarian-Teacher Identity - Cadogan, Dawn; Campbell Rice, Brynne; Maher, Stephen; Torian, Stacy (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2023)
Teaching is one of the most consequential responsibilities of an academic librarian, yet many of us approach it without the training or self-awareness required to do it well. Teaching well means being willing to commit to endless, fearless exploration of pedagogical pathways, shifting social realities, and discomforting valleys within the self. These journeys enable us to define and strengthen our teacher identities. Critical LIS studies on identity frequently explore the multiplicity of librarian attitudes toward teaching or the complexity of individual librarian identities. In our study, we merged these two exploratory objectives by analyzing the dialogical interaction of an academic librarian's multiple identities in the teaching context, specifically. As academic librarians, diverse in terms of race, gender, age, and professional experience, we engaged in collaborative autoethnography to uncover and name the interlocking identities that inform our teaching endeavours. Through the lens of dialogical self theory (DST) and its concept of self positioning, we identified positions of the self that interact and negotiate with each other to facilitate or complicate the act of teaching itself. Autoethnographic exploration deepened our understanding of our teaching selves and helped us decipher the socio-psychological scripts that hinder and empower us as educators.